Antibacterial Activity and in-vivo Protection Potentials of Aspergillus Species SK2 Antibiotic Substance against the Establishment of Infections By ?- Lactamase Producing Clinical Bacteria - Ekong, Ubong S.; Obi, Samuel K. C. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Antibacterial activity of an Aspergillus species SK2 (AS – SK2) antibiotic substance against ?-lactamase producing bacteria assayed by agar-well diffusion technique, indicated broad-spectrum of activity with significant (P < 0.05) high potencies compared with the controls against Staphylococcus aureus(SA): Staphylococcus epidermides, Staphylococcus saprophyticus (SS); ?-lactamase-positive (methicillin-resistant) Staphylococcus aureas (MRSA); Bacillus subtilis (BS); Streptococcus pyogenes (SP); Escherichia coli (EC)’ Salmonella typhi (ST); Pseudomonas aeruginosa( PA); Shigella dysentariae (SD); Vibrio cholerae (VC) Klebsiella pnuemoniae (KP); Proteus mirabilis (PM).The mode of activity of the agent assayed by macrobroth dilution technique, indicated bacteriostatic activity with high stability or potency to ?- lactamase activity and relatively low MIC (0.06 mg/ml P.E) for SS, MRSA, SP, ST, SD and VC; but higher for both EC (0.24 mg/ml P.E) and PA (0.48 mg/ml P.E) respectively compared with the control. The antibiotic substance was relatively non-toxic with an LD50 of 3.8 mg/ml P.E/Kg and a large therapeutic index of 7.92. The AS-SK2 agent offered high rate of protection to the experimental animals challenged intraperitoneally with both the pathogens and antibiotics substances against the successful establishment of the infections by the ?- lactamase producing Gram-positive and Gram-negative bacteria. Of particular interest is the activity against the MRSA which recorded 100% protection, while EC only recorded 33.3% protection and PA recorded no protection but 100% mortality.